Modulating Dynamic Photoresponse Behavior of Organic Phototransistors Through Morphology Control - Weijie Gong; Di Xue; Chi Yan; Yao Yin; Yingying Zhang; Jie Lu; Jichao Jiang; Jidong Zhang; Yuran Xiao; Feng Ding; Zi Wang; Lizhen Huang; et al. (Advanced Electronic Materials)
Abstract Organic phototransistors (OPTs) show great promise in optoelectronic applications, including memory devices, logic circuits, and neural networks, due to their effective photoelectric conversion and signal amplification capability. While most OPTs exhibit photomemory behavior, achieving a photoswitching response typically requires specific materials or a unique device structure. However, modulating between photomemory and photoswitching behavior within a single system is crucial for creating versatile, directionally functional devices. In this study, a straightforward approach is demonstrated to tune the response from photomemory to photoswitching in a single OPTs by adjusting the growth process of organic semiconductor. The findings show that the dynamic photoresponse is strongly linked to the film ordering, with reduced crystalline quality favoring photoswitching behavior and highly crystalline quality tending photomemory behavior. This shift correlates closely with changes in the properties and density of trap states in the active layers, as confirmed by Kelvin probe force microscopy (KPFM). Overall, this study introduces a simple, effective method to control the photoresponse of OPTs, enhancing the potential application of organic optoelectronic devices.